Love's Labour's Lost - David, Richard (Methuen, 1956)
The Library of Congress, William Shakespeare's "Love's Labour's Lost," a reading staged by Arnold Moss, presented under the auspices of the Gertrude Clarke Whittall Poetry and Literature Fund, production stage manager, Seymour Milbert, costume superviser Ruth Frank.